Cystic Fibrosis Atypical Forms Presentation: Edema, Anemia and Skin Lesions - Chabelys de la Caridad Rodríguez Membrides; Carlos Enrique Cruz Carrazana; Milda Díaz Martínez (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Cystic fibrosis or mucoviscidosis is the most common genetic disease in the Caucasian race characterized by thickening of secretions due to abnormal ion transport of epithelial cells, manifested with pancreatic insufficiency, progressive lung disease, alteration in the secretion of electrolytes in sweat, azoospermia in males and decreased fertility in females. Treatment of cystic fibrosis is primarily symptomatic. A case of a two-and-a-half-month-old infant who began to present vomiting, scattered and scaly irregular erythematous lesions on the skin on the face, chest, limbs, anal and genital region, in addition to presenting little weight gain is presented. For these reasons it was decided to admit her for study and treatment. A physical examination, complementary tests, of the cardiovascular system was performed. A diagnosis of cystic fibrosis and gastroesophageal reflux was made. This case is presented for describing the clinical and laboratory characteristics of a patient with atypical presentation of cystic fibrosis. Skin alterations as a presenting sign of cystic fibrosis are rare and only fewer than 30 cases have been reported in the medical literature.